Special employment centers in Castile and León 2007-2013: effects of the crisis in relation to these centers’ registered legal personalities - Manzano Martín, María Isabel; Redondo Martín, María Nieves; Robles Paramio, María Paz (REVESCO. Revista de Estudios Cooperativos, 2016)
The aim of this paper is to carry out an economic and financial study of the Special Employment Centres in Castile and León based on a classification of these entities’ registered legal personalities in order to view how the economic crisis that began at the end of 2007 may have affected them. Various items from the Centres’ financial statements are analysed and the results are compared to those from the period 2007-2013 as to provide a broader perspective of their size, development, growth and behaviour. The following economic figures were used: total assets, turnover and revenue. The variable “employment” is compared with the subsidies received by the Centres, showing that the crisis does affect the Centres depending on their registered legal personalities. Associations and physical persons are the most affected personalities, to the point of possible extinction. An account reversal for the Centres is also included in this article, which measures the percentage of public aid received by the Centres that is returned to society.